STRUCTURAL VALIDITY OF R-SPQ-2F: A CONFIRMATORY FACTOR ANALYSIS - Merino Soto, Cesar (2013)
The aim of this study is to validate the internal structure of the Revised-Study ProcessQuestionnaire-2 Factors (Biggs, Kember & Leung, 2001), through a heterogeneous sampleof 269 university and non-university participants. The structural equation methodology isused to test several measurement models: one-dimensional, four factors and hierarchicalstructure, and two factors (orthogonal and oblique).Theodels based on four factors did notshow a satisfactory adjustment, and one had convergence problems caused by a very highinterfactorial correlation. The two-factor model (deep and shallow) with correlated errorshad a satisfactory adjustment. The internal consistency was satisfactory. The usefulness ofthe instrument and its theoretical reformulation is discussed.